ANALISIS KORELASI KANONIK KUALITAS PELAYANAN DAN KEPUASAN KONSUMEN PADA MIE MIELIADER BANDUNG - Fitria Dwi Nuriyah; Rendra Erdkhadifa (Bajang Institute, 2023)
Consumer satisfaction is consumer expectations of a product. Customer satisfaction can be created by paying attention to the quality of service. The higher the quality of service and customer value obtained, the greater the customer satisfaction. This study aims to find out whether there is a relationship between service quality and customer satisfaction at Mie Mieliader Bandung. The approach used in this study is a quantitative approach with a canonical correlation analysis method. The data used are primary data with sampling quota sampling techniques in the form of distributing questionnaires to the target population. Variable indicators of service quality include reliability, physical evidence, responsiveness, assurance, and empathy. Variable indicators of consumer satisfaction include product quality, price, emotional factors and convenience. The results obtained in this study show that the quality of services provided by Mie Mieliader Bandung has a close relationship with consumer satisfaction. The variable indicator of service quality that has the greatest influence is assurance, while the indicator of consumer satisfaction, namely product quality, is the variable that has the greatest influence.